2015
DOI: 10.1007/s12540-015-1015-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basicity and B2O3 on viscosity, melting and crystallization behaviors of low fluorine mold fluxes for casting medium carbon steels

Abstract: As potential substitutes for fluorides, the influences of basicity and B2O3 content on viscosity, melting and crystallization behaviors of low fluorine mold fluxes for casting medium carbon steels were investigated by using Brookfield viscometer and Single Hot Thermocouple Technique in this study. Results suggested that, the break temperature, crystallization temperature and critical cooling rate of low fluorine mold fluxes were increased with the increase of basicity; while they were decreased with the furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…[25][26][27][28] And, it was divided into two parts; the first part is about melting and heat transfer behaviors; while the second part is focused on the study of viscosity and crystallization behavior of F-free mold fluxes for medium carbon steels continuous casting. This is the second part with the aim to investigate the viscosity and crystallization behavior of F-free mold fluxes.…”
Section: 24)mentioning
confidence: 99%
“…[25][26][27][28] And, it was divided into two parts; the first part is about melting and heat transfer behaviors; while the second part is focused on the study of viscosity and crystallization behavior of F-free mold fluxes for medium carbon steels continuous casting. This is the second part with the aim to investigate the viscosity and crystallization behavior of F-free mold fluxes.…”
Section: 24)mentioning
confidence: 99%
“…A calibration measurement was carried out at room temperature by using stand oil with a known viscosity. [29] During the viscosity measurement test, first, about 250 g of the sample powders were placed in a graphite crucible with a diameter and internal height of 50 and 80 mm, respectively. Second, the crucible was heated to 1773 K (1500°C) and held for 10 minutes to obtain a homogeneous melt in an electric resistance furnace with MoSi 2 as the heating element.…”
Section: Lejun Zhou and Wanlin Wangmentioning
confidence: 99%
“…Thus, these fluorides will lead to the corrosion of equipment, serious environmental pollution, etc. [6,7] Therefore the development of new environmental friendly F-free mold fluxes is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Nakada et al [3,7,8] studied the crystallization behaviors of CaO-SiO 2 -TiO 2 slag system and their results suggested that the precipitate CaOAESiO 2 AETiO 2 in the F-free mold flux could be a substitute for cuspidine. However, Wang et al found that the formation of the high melting point compounds such as TiN and Ti(C,N) in the liquid slag during the casting process may cause the increase of viscosity, break temperature, T br and crystallization temperature, which leads to a lack of lubrication and the tendency of sticker breakout.…”
Section: Introductionmentioning
confidence: 99%